2017
DOI: 10.1021/acs.jpcc.7b04207
|View full text |Cite
|
Sign up to set email alerts
|

Single Emitter Fluorescence Enhancement with Surface Lattice Resonances

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 54 publications
(111 reference statements)
2
29
0
Order By: Relevance
“…The spectral position of this peak, in fact, is mainly dictated by the value of the lattice period and marginally by the geometric dimensions of the dimers. Similar effects have been already noticed in periodic arrays of plasmonic antennas 15 and in arrays of dielectric nanowires 14 . Nevertheless, according to our knowledge, this is the first attempt to combine the SLR with the local resonances of dielectric dimers to tailor an engineered substrate for SERS application.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The spectral position of this peak, in fact, is mainly dictated by the value of the lattice period and marginally by the geometric dimensions of the dimers. Similar effects have been already noticed in periodic arrays of plasmonic antennas 15 and in arrays of dielectric nanowires 14 . Nevertheless, according to our knowledge, this is the first attempt to combine the SLR with the local resonances of dielectric dimers to tailor an engineered substrate for SERS application.…”
Section: Resultssupporting
confidence: 80%
“…However, the EF of a single dielectric dimer has been shown to reach levels consistently below the levels of plasmonic scatterers. Dimers placed in a periodic array were already studied and it has been shown that Surface Lattice Resonances (SLR) are present 14,15 . These resonances are narrow band and Fano line shaped.…”
Section: Introductionmentioning
confidence: 99%
“…Strong coupling between lattice modes in arrays of nanoparticles (NPs) and Mie-type oscillations localized within a single NP, has attracted significant attention over the last decade. Pioneering theoretical predictions for 1D arrays of Ag NPs [1-3] and consequent experimental verification for 2D arrays of Au NPs [4][5][6] have given a momentum to a great number of excellent applications of collective lattice resonances in lasers [7][8][9][10][11][12], biosensors [13][14][15][16][17][18], emission enhancement [19][20][21][22], and color printing [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…[171] Condensed phase MVCD for a long time resisted thorough quantum chemical analysis, and available models explained it only qualitatively. [12,172,173] This changed in 2018 when MVCD intensities could be reproduced using common quantumchemical software (Figure 7). [13] The MVCD theory, similarly as for (electronic) MCD is based on the transition electric dipole moments perturbed by the magnetic field.…”
Section: Magnetic Vibrational Circular Dichroismmentioning
confidence: 99%